2011
DOI: 10.1038/onc.2011.307
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypermethylation in lung cancer is targeted at differentiation-associated genes

Abstract: Aberrant DNA hypermethylation of tumor suppressor genes is thought to be an early event in tumorigenesis. Many studies have reported the methylation status of individual genes with known involvement in cancer, but an unbiased assessment of the biological function of the collective of hypermethylated genes has not been conducted so far. Based on the observation that a variety of human cancers recapitulate developmental gene expression patterns (that is activate genes normally expressed in early development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
5
17
0
Order By: Relevance
“…Hypermethylated genes were enriched for developmental and differentiation-associated processes and polycomb targets premarked by histone H3K27 trimethylation in embryonic cells (24,25). These results are consistent with a hypothesis that DNA methylation in lung cancer preferentially targets genes involved in morphogenetic processes and late stage differentiation of the lung epithelium, potentially contributing to establishment of an early undifferentiated cancer phenotype (24).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hypermethylated genes were enriched for developmental and differentiation-associated processes and polycomb targets premarked by histone H3K27 trimethylation in embryonic cells (24,25). These results are consistent with a hypothesis that DNA methylation in lung cancer preferentially targets genes involved in morphogenetic processes and late stage differentiation of the lung epithelium, potentially contributing to establishment of an early undifferentiated cancer phenotype (24).…”
Section: Discussionsupporting
confidence: 79%
“…1A). Correlation analyses of DNA methylation and gene expression revealed a pattern of negative correlations at transcription start sites and more positive correlations in Functional annotation analysis of genes with hypermethylated CpGs in the 4136 CpG set showed enrichment of biologic processes such as regulation of transcription, neural development, and cell morphogenesis corroborating previous studies (24,25), whereas hypomethylated genes showed a much less clear functional enrichment (Supplementary Table S2). …”
Section: Genome-wide Dna Methylation Patterns In Lung Cancersupporting
confidence: 73%
“…Hypermethylated genes were mainly found to be related to developmental processes along the lines of/similar to those found in previous studies of other cancer types (45,46). However, hypomethylated genes were enriched for GO terms associated with the immune system.…”
Section: Discussionsupporting
confidence: 54%
“…Gene ontology analysis of the genes associated with these DMRs revealed that the aberrantly hypermethylated genes primarily belonged to categories related to nucleic acid binding, DNA binding, and activation of transcription factors, suggesting that the methylation of these affected genes coupled with the downregulation of RNA expression resulted in the decreased expression of other genes. Studies of non-small-cell lung carcinoma by Helman et al [14] and Zhao et al . [15] demonstrated that methylation-enriched genes displayed aberrant methylation and RNA expression in multiple tumor types; these genes were referred to as tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%